Curtindo, pegando, largando: relacionamentos e sociabilidades no forró contemporâneo - Scott, Amanda Martha Campos (2014)
This study assumes that music and sociability are interconnected, with an exchange between them, intercommunication. The author seeks to understand how a forró band in evidence today, “Wesley Safadão and Garota Safada” (re)interpret the affective-sexual relations in how they represent sex and romance in contemporary Northeastern-Brazil society. To do so, different facets of forró must be understood, which, besides music, involves dance, spaces of socialization, and a context of production and performativity peculiar to the interaction of the show/event. It is noticed that many authors have turned their attention to this cultural product, raising criticism about its content and its quality, and generating tension in the music market, as well as in the academic field, with different perspectives on electronic forró. Making use of participant observation, this band´s show experience reviews particularities, involving a public circuit of forró and different ways of “enjoying” and relating to others, considering both the festive sociability and the message of the music. Through content analysis of two DVDs of the band (“Uma Nova História”, 2012; “Garota Vip”, 2013), affective-sexual relations were identified in nuances of “Enjoying, Picking, Letting-go”. The lyrics represent such relations and recurring elements could be identified, highlighting trends and themes reinforced during the shows as shared ideas, and recognized by the audience, for whom the process “enjoy/pick/let-go” reflects their perspective of affective and sexual relations idealized or experienced at the events and/or in daily life. Keywords: Events. Forró. Relations. Gender.This study assumes that music and sociability are interconnected, with an exchange between them, intercommunication. The author seeks to understand how a forró band in evidence today, “Wesley Safadão and Garota Safada” (re)interpret the affective-sexual relations in how they represent sex and romance in contemporary Northeastern-Brazil society. To do so, different facets of forró must be understood, which, besides music, involves dance, spaces of socialization, and a context of production and performativity peculiar to the interaction of the show/event. It is noticed that many authors have turned their attention to this cultural product, raising criticism about its content and its quality, and generating tension in the music market, as well as in the academic field, with different perspectives on electronic forró. Making use of participant observation, this band´s show experience reviews particularities, involving a public circuit of forró and different ways of “enjoying” and relating to others, considering both the festive sociability and the message of the music. Through content analysis of two DVDs of the band (“Uma Nova História”, 2012; “Garota Vip”, 2013), affective-sexual relations were identified in nuances of “Enjoying, Picking, Letting-go”. The lyrics represent such relations and recurring elements could be identified, highlighting trends and themes reinforced during the shows as shared ideas, and recognized by the audience, for whom the process “enjoy/pick/let-go” reflects their perspective of affective and sexual relations idealized or experienced at the events and/or in daily life.